Hydrological dynamics and water resource availability in the Rift Valley Lakes Basin (Ethiopia), using a WEAP model - Mulugeta Mohammed; Belete Birhanu; Fentaw Abegaz (Water Practice and Technology, 2024)
This study aims to assess hydrologic dynamics and the water resource potential of the Rift Valley Lake Basin (RVLB) in Ethiopia using the Water Evaluation and Planning System (WEAP) model. The surface water of the RVLB comprises streamflow and an open water system. The model was configured with 13 catchments and a monthly time series of approximately 43 years (1981–2022) to address the spatial variability of rainfall-runoff interaction. Statistical performance indicators were used to evaluate the accuracy of the model in simulating streamflows, and the results showed that the coefficient of determination (R2) ranges from 0.82–0.93, Nash-Sutcliffe coefficient of efficiency (NSE) ranges from 0.68–0.86, percentage of bias (PBIAS) ranges from –9.45 to –1.85, standard deviation ratio (RSR) ranges from 0.35 to 0.59 and index of agreement (IA) ranges from 0.62 to 0.84. The available surface water for abstraction is estimated to be 358 million cubic meters (MCM) available as lake water abstraction, and 6,534 MCM as streamflow water, making it a total surface water flow of 6,892 MCM. Considering the temporal distribution of the surface water sources, 67.5% is available in the rainy season, June–October, and 32.5% during the dry period, November–May, in the basin. HIGHLIGHTS It solves the knowledge gap regarding the potential water resource availability of the basin with a comprehensive assessment.; The findings of this research can be used for planning water resources.; The WEAP model is used with appropriate data input for calibration and validation which make thoroughness and validity of the research.; It can be used as a literature for studies.; It indicated research gaps for further studies;